1994
DOI: 10.1136/gut.35.7.961
|View full text |Cite
|
Sign up to set email alerts
|

Observer variation and discriminatory value of biopsy features in inflammatory bowel disease.

Abstract: If skilled histopathologists disagree over the same biopsy specimen, at least one must have an incorrect interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
2
16

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(150 citation statements)
references
References 19 publications
6
124
2
16
Order By: Relevance
“…Diffe rentiating between subtypes of IBD sometimes has a degree of uncertainty due to overlapping clinical and pathological features [1] . Despite clinical evaluation, radiological, endoscopic and histopathological testing by expert physicians, up to 20% of IBD cases are classified as "indeterminate colitis" or "IBD undifferentiated" [2,3] . However, accurate classification of IBD is essential as response to medication, surgical indications and prognosis can vary between UC and CD [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Diffe rentiating between subtypes of IBD sometimes has a degree of uncertainty due to overlapping clinical and pathological features [1] . Despite clinical evaluation, radiological, endoscopic and histopathological testing by expert physicians, up to 20% of IBD cases are classified as "indeterminate colitis" or "IBD undifferentiated" [2,3] . However, accurate classification of IBD is essential as response to medication, surgical indications and prognosis can vary between UC and CD [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Tsang, (1999) reported that there are major and minor criteria for the diagnosis of UC, the major ones were: patchy mucosal inflammatory infiltrate, basal plasmacytosis, neutrophils overrunning mucosa, crypt abscesses, cryptitis, crypt distortion and villiform surface, while the minor criteria were: decreased goblet cells, and Paneth cell metaplasia.(23). Theodossi, et al (1994), suggested that a decrease in mucous content, an irregular or a villous surface, crypt distortion, diffuse crypt abscesses, and cryptitis are predictive of ulcerative colitis rather than of Crohn's disease. (24).…”
Section: B a A B C Dmentioning
confidence: 99%
“…Theodossi, et al (1994), suggested that a decrease in mucous content, an irregular or a villous surface, crypt distortion, diffuse crypt abscesses, and cryptitis are predictive of ulcerative colitis rather than of Crohn's disease. (24).…”
Section: B a A B C Dmentioning
confidence: 99%
“…Severity in ulcerative colitis is generally assessed using symptoms, laboratory data [47] , colonoscopic findings [48][49][50][51][52][53][54][55] and histologic degree of inflammation in the biopsy specimens [15,[56][57][58][59] . Histopathologic assessment is considered the standard for evaluation of disease activity in patients with ulcerative colitis [60] .…”
Section: Prediction Of Relapse In Patients With Quiescent Ulcerativementioning
confidence: 99%